PENGGUNAAN PUZZLE SEBAGAI MEDIA EVALUASIPENGUASAAN MUFRODAT DALAM PEMBELAJARAN BAHASA ARAB DI MADRASAH TSANAWIYAH - Arrayyan, Ahmad Faris; Suparmanto, Suparmanto; Elidatunnisa, Iin; Handayani, Losi; Syarif Hidayatullah, Muhammad (Al-Maraji' : Jurnal Pendidikan Bahasa Arab, 2024)
Mufrodat (vocabulary) is one of the important elements in learning Arabic. Even some opinions say the first thing in learning a foreign language is to recognize and learn vocabulary. Although language learning will not be enough if you only learn vocabulary without paying attention to grammar and the language system itself. By studying mufrodite, it will be possible for students to acquire language skills (istima, kalam, qiroah, kitabah). To find out the extent of the achievement of learning objectives, it is necessary to evaluate. Where the evaluation is carried out by examining the extent of students' ability to use mufradat. This study aims to describe the results of learning to use puzzles with word wall media at Madrasah Nurul Anwar. This type of research is descriptive qualitative research. Data collection techniques used are by interviewing, observing, and presenting data.